HUBUNGAN FAKTOR RESIKO HIV/AIDS DENGAN PELAKSANAAN VCT DI KTH (KLINIK TES HIV/AIDS) MANDALIKA RSUD PRAYA TAHUN 2013 - Fitra Arsy Nur Cory’ah; Ni Putu Dian Ayu Anggraeni; Wahyu Wirawan Triyono (Jurnal Kesehatan Prima, 2014)
Abstract: The relationship of unsafe sex, the use of unsterile needles and in turn, infected blood transfusions, and transmission of HIV-infected mother to child at birth are risk factors that can transmit HIV from one person to another. With VCT services, communities especially the population at risk and their family members can find out their status of HIV-related health as a motivation of transmission prevention efforts and to accelerate them acquiring health aid as needed. Central Lombok district ranks fourth in HIV and AIDS cases in the province of West Nusa Tenggara (NTB). This study uses correlation and analytic methods with cross sectional survey. Sample collection was accidental i.e. by taking respondents who happened to be at the time of the mobile VCT KTH Mandalika Praya Hospital researchers who fit the criteria. The instrument used in this study was questionnaire. The result for HIV- AIDS risk factors by implementing VCT showed p value = 0.012 < α = 0.05, this means there is a significant association between the risk factor (unsafe sexual behavior) with the implementation of VCT, so it is advised to health workers to improve their approach in the provision of counseling and motivation on HIV / AIDS especially on VCT services to reduce the transmission of HIV / AIDS.